Carbon Pricing for Climate Action - World Bank Group (World Bank, Washington, DC, 2021)
Carbon prices are needed to incorporate climate change costs into economic decision making. Carbon pricing should be included as part of a broader arsenal of tools to achieve domestic climate targets, but it is not a silver bullet: other policy instruments and investments (for example, public transport, power transmission infrastructure) are needed to complement carbon pricing and to enable consumers to respond to higher prices by switching to lower emission alternatives. A carbon tax can be effective in smaller economies with human capacity constraints and in jurisdictions with well-established and transparent tax frameworks. Emission trading systems may be chosen by larger, more established, and market-linked economies with political economy barriers to tax reform. Successful carbon pricing reforms require integrating many stakeholders’ considerations and increasing the capacity of governments and domestic businesses. The World Bank Group, through its climate change action plan, is well positioned to leverage its convening power, knowledge and research, and country program support to help countries make informed decisions on carbon pricing policies, their design, and implementation.